Modernism : an anthology - Rainey, Lawrence S. (Blackwell, 2005)
Modernism: An Anthology is the most comprehensive anthology of Anglo-American modernism ever to be published. * Amply represents the giants of modernism - James Joyce, Gertrude Stein, Virginia Woolf, T.S. Eliot, Ezra Pound, Wallace Stevens, Marianne Moore, Samuel Beckett.